1875 Mo. Laws 50-51, An Act to prevent the carrying of weapons in public assemblies of the people, and to repeal "An Act to prevent the carrying of concealed weapons," approved March 26, 1874, § 1 - (:unkn) unknown (General Publisher, 1875)
Prohibited concealed carry of any fire-arms, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon in any church, place of religious worship, school-room, assembly for educational, literary, or social purpose, election precincts on election day, or court-room while court is in session, or into any other public assemblage of persons met for purposes other than miltiia drill or under militia law.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES